ANALISIS TINGKAT POTENSI FINANCIAL DISTRESS MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 SAMPAI 2018 - Utari, Aprilia Winda; Makhdalena, Makhdalena; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to analyze the condition of the company using the Altman Z-Score method in predicting potential financial distress in the Food and Beverage Sector Manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. Sampling using purposive sampling technique with a sample of 11 manufacturing companies in the food and beverage sector. drink. This study uses secondary data obtained from the company's annual reports from 2014 to 2018. The analysis technique used is descriptive analysis with the Altman Z-score bankruptcy prediction model. The results of this study indicate that from 2014 to 2018 of 11 manufacturing companies in the food and beverage sector, there were 3 companies that were included in the category of potential bankruptcy based on their Z-score of less than 1.81. Of the 11 companies, there were 5 companies that experienced a gray area where the company's Z-score was between 1.81-2.99. There are 5 companies that are in the healthy category for five consecutive years where the company's Z-score is always above 2.99.Key Words: Altman Z-score, Financial Distress, Food and Beverage Sector ManufacturingCompanies